Chemotherapy in the Last 30 Days and 14 Days of Life in African Americans With Lung Cancer. (August 2021) - Johnson, Lee Ann; Ellis, Charles
Background: African Americans with lung cancer are diagnosed at later stages and have high mortality rates. Chemotherapy is considered aggressive treatment near the end of life and prevents enrollment in hospice. Objectives: This study explored chemotherapy in the last 30 and 14 days of life among African Americans with lung cancer. Methods: A retrospective chart review was used to gather sociodemographic and treatment data on persons newly diagnosed with lung cancer between January 1, 2016 and June 30, 2017. African Americans with a documented date of death were included. Results: The mean age (N=74) was 64.0 years, 58.1% were rural dwellers, and 59.5% had Medicare. Most had advanced stage non-small cell lung cancer (Stage IIIB, 18.8%; Stage IV, 46.4%). In this study, 17.6% received chemotherapy in the last 14 days of life and 27.0% received chemotherapy in the last 30 days of life. No significant associations between age, sex, residence (rural vs urban) and receipt of chemotherapy in the last 14 or 30 days of life were found. A significant association was found between type of insurance and chemotherapy in the last 14 or 30 days of life: Medicare was associated with chemotherapy in both last 14 days of life χ 2 (1) = 4.448, p = .035 and last 30 days of life χ2(1) = 4.773, p = .029. A binomial logistic regression using demographic factors, including insurance, was not significant. Conclusion: Our results indicate a need for improvement in the number of individuals who receive chemotherapy in the final month of life.